F(x)=5(x-2)(x-3)

Simple and best practice solution for F(x)=5(x-2)(x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for F(x)=5(x-2)(x-3) equation:


Simplifying
F(x) = 5(x + -2)(x + -3)

Multiply F * x
xF = 5(x + -2)(x + -3)

Reorder the terms:
xF = 5(-2 + x)(x + -3)

Reorder the terms:
xF = 5(-2 + x)(-3 + x)

Multiply (-2 + x) * (-3 + x)
xF = 5(-2(-3 + x) + x(-3 + x))
xF = 5((-3 * -2 + x * -2) + x(-3 + x))
xF = 5((6 + -2x) + x(-3 + x))
xF = 5(6 + -2x + (-3 * x + x * x))
xF = 5(6 + -2x + (-3x + x2))

Combine like terms: -2x + -3x = -5x
xF = 5(6 + -5x + x2)
xF = (6 * 5 + -5x * 5 + x2 * 5)
xF = (30 + -25x + 5x2)

Solving
xF = 30 + -25x + 5x2

Solving for variable 'x'.

Reorder the terms:
-30 + 25x + xF + -5x2 = 30 + -25x + 5x2 + -30 + 25x + -5x2

Reorder the terms:
-30 + 25x + xF + -5x2 = 30 + -30 + -25x + 25x + 5x2 + -5x2

Combine like terms: 30 + -30 = 0
-30 + 25x + xF + -5x2 = 0 + -25x + 25x + 5x2 + -5x2
-30 + 25x + xF + -5x2 = -25x + 25x + 5x2 + -5x2

Combine like terms: -25x + 25x = 0
-30 + 25x + xF + -5x2 = 0 + 5x2 + -5x2
-30 + 25x + xF + -5x2 = 5x2 + -5x2

Combine like terms: 5x2 + -5x2 = 0
-30 + 25x + xF + -5x2 = 0

The solution to this equation could not be determined.

See similar equations:

| c/4-31=10 | | 3w-3+w=7 | | 62+67+x+90=360 | | 8=288-7x | | 3x^5-27x^3+54x=0 | | -5(1+6n)=-5 | | 2+67+x+90=360 | | 5x-10y=100 | | 8z=8z | | c/4-17=6 | | 82+67+6+90=360 | | 10+5y-2y-6= | | -25=5(-n+1) | | 20y-10yz= | | A+b+s+s+e= | | 1nx=-1 | | 4x=.5x+5 | | 33+6+77+100=360 | | 1nx=1 | | A+b+s+s+e=sb | | 2.25=0 | | F(x)=3cos(2x)+1 | | 2x+4-8x=28 | | G(3b)=3b^2-3b | | 3x+10+z+32=180 | | 0.2x+1.9=0.9 | | 2(3d-4)+10=5d+7 | | 4x+.33=.5x+5.33 | | -r/11=36 | | 12=1/5x | | F(3)=4x+9 | | 12=3(v-2) |

Equations solver categories